Intensive training and cardiac autonomic control in high level athletes - Bonaduce, D.; Petretta, M.; Cavallaro, V.; Apicella, C.; Ianniciello, A.; Romano, M.; Breglio, R.; Marciano, F. (Medicine & Science in Sports & Exercise, 1998)
We aimed to evaluate in a longitudinal study the effect of intensive training on cardiac autonomic control in athletes using 24-h heart rate variability analysis. This study demonstrates that an increased cardiac vagal control is detectable in detrained athletes; however, after intensive training, despite a significant decrease in heart rate, time and frequency domain measures of heart rate variability reflecting cardiac vagal control remain unchanged. Thus, other mechanisms than changes in cardiac autonomic control could be involved in determining the profound bradycardia of athletes.